Preface to the Special Issue (Journal of the Digital Humanities Association of Southern Africa, 2023)
The editors are happy to present the first special issue of the Journal of the Digital Humanities Association of Southern Africa (DHASA). In this issue, we bring together articles from the field of Digital Humanities with the underlying theme “Crossroads DH”. Under this umbrella topic, we investigate the manifold connections of Digital Humanities with academic disciplines that are not usually connected with Digital Humanities. This also includes research on comparative Digital Humanities studies of different datasets, and hands-on or analytical work in the sciences where Digital Humanities methods or approaches are applied. Additionally, this issue contains practical examples of the application of Digital Humanities and their application to real life problems.
Keywords: Special Issue 2022; Preface; Editorial